Fair prices for fair wages in the agro-food chain: is farm production efficiency the missing link? Evidence from the processing tomato sector in Italy - Marchini, Andrea; Ciliberti, Stefano; Gastaldin, Nadia; Turchetti, Luca; Martino, Gaetano (Frontiers in Sustainable Food Systems, 2024)
It is usually believed that the position of farmers along the agro-food supply chains is weak, and this circumstance leads farms to achieve modest prices for their products and, in turn, to capture only a small share of the added value. Such a situation substantially limits farms effort to adequately remunerate the resources employed, including contract and hired labour. This article argues that, while the unfavourable position of farms is a valid concern, it is also crucial to consider how an efficient use of resources employed in agriculture impacts on their remuneration, by means of price mechanisms. An empirical analysis conducted on a FADN sample of farms producing processing tomato over the years 2014-2018 reveals that the product price which allows for an adequate compensation of hired agricultural labour decreases with increasing efficiency. At the same time, all other things being equal, for price levels above the theoretical one, the profit of the farms increases and possibility for fairer wages as well.